TEORI MAQÂSHID SYARÎ’AH PERSPEKTIF AL-SYATIBI - Toriquddin, Moh (Fakultas Syariah, 2014)
The discourse surrounding the theory maqÃ¢shid syarÃ®'ah is still worth doing it aims to understand who far Islamic lawÂ is in lineÂ with theÂ progress of time. Theory maqÃ¢shidÂ syarÃ®â€Ÿah Syathibi globally based on twoÂ things: the problems ta'lil (legal determination basedÂ illat), andÂ al-mashÃ¢lihÂ waÂ al-mafÃ¢sidÂ (benefitÂ andÂ damage). Furthermore, he explains howÂ to determine maqÃ¢shid with six ways: goals syari'ah must beÂ in accordanceÂ with theÂ Arabic language,Â commandsÂ andÂ prohibitions syarÃ®â€Ÿah understood as ta'lÄ«l (have illat) and á¸ahiriyah (text what it is), maqÃ¢shid al-ashliyahÂ (originÂ destination)Â waÂ al-maqÃ¢shidÂ al-tabi'iyyahÂ (destinationÂ followers), sukut al-syÃ¢riâ€ŸÂ (silenceÂ syÃ¢riâ€Ÿ), al-istiqra'Â (theory of induction), looking for clues of the CompanionsÂ of the Prophet.Â For operatingÂ of ijtihadÂ al-Â maqÃ¢shidy,Â Syathibi requires four conditions as follows: texts and laws depending on the goal, collecting betweenÂ kulliyÃ¢tÂ al-'Ã¢mmahÂ andÂ specificÂ arguments,Â bringÂ benefitÂ and prevent damage to the absolute and considering the result of a law.